Inteligência artificial e a ilusão do percepto afetivo - Fusaro, Alberto Cabral (2018)
Our investigation fits into a branch of Artificial Intelligence research, namely the Weak AIs subset, aiming to figure out the way that these AIs are applied in videogames development – we call it just “games”, referring to all games that run on any form of electronics platform. Our focus bears on a strict human-behavior simulation system that goes on the market by the name of Drivatar, a system-controlled virtual-entity whose operation is based on machinelearning technology. They were developed by Microsoft and Turn10 Studios to perform as “simulated human” pilots in their Forza Motorsport automotive-racing franchise games. Our goal is to identify the main AI elements and their application strategies that enable them to create the illusion of humanity, making the players believe that they are their human counterparts instead of simulations